The speed of the snail: The Zapatistas' autonomy de facto and the Mexican state - Ana C. Dinerstein (University of Bath, Centre for Development Studies (CDS), 2013)
The recent re-emergence of autonomy as a central demand in many social movements across the world (which involve claims for self-determination, organisational self-management and independence vis-à-vis the state and capital) has opened a theoretical space to re-think its meanings in novel ways. Particularly interesting are in this regard autonomous practices, which have been presented by movements as offering an alternative to social relations of capitalism. In this paper I offer an illustrative case study of new political and juridical bodies (the 'Snails' and Good Government Council) operated by the Zapatista movement in the Chiapas region, Mexico. I use this case to illustrate the Zapatista's struggle for autonomy with, against and beyond the Mexican State, and the role of the law and policy making in disciplining the rebel communities of Chiapas. By exploring the Zapatistas' critique of civil society and development, I engage with Bloch's 'principle of hope' in order to theorise autonomy as a form of 'organising hope'. I suggest that autonomy delineates spaces where a utopian impulse is articulated, made concrete, realised, experienced, and also disappointed. The data presented comes from the author's research project on social movements and collective autonomy in Latin America (RES-155-25-0007) funded by the 'Non-Governmental Public Action' programme of the Economic and Social Research Council, United Kingdom.
Keywords: 330; Autonomy; Bloch; civil society; development; hope; Zapatistas; Mexico